2016
DOI: 10.1111/ruso.12124
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Better Food Access? The Role of Farmers' Markets in the U.S. Local Food Movement

Abstract: The local food movement has grown substantially in the United States in recent years. Proponents have hailed this growth as a shift away from a conventional food system rife with inequality toward one that introduces more just outcomes for society. While the movement's development and popularity have proliferated, little research has examined nationally how successful it is at delivering on its promises. By combining the social movement and food system literatures with quantitative methodology, this article ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 94 publications
(149 reference statements)
0
11
0
2
Order By: Relevance
“…It is generally understood that living in a food desert increases the risk of developing dietrelated chronic diseases such as obesity (Brace et al, 2020;Schupp, 2017Schupp, , 2019. Research shows that, although farmers' markets serve as community-level interventions that provide healthy food options to food deserts (Brace et al, 2020;, farmers' markets are infrequently found where they are most needed (Schupp, 2019).…”
Section: Marketplaces As Be Interventionsmentioning
confidence: 99%
“…It is generally understood that living in a food desert increases the risk of developing dietrelated chronic diseases such as obesity (Brace et al, 2020;Schupp, 2017Schupp, , 2019. Research shows that, although farmers' markets serve as community-level interventions that provide healthy food options to food deserts (Brace et al, 2020;, farmers' markets are infrequently found where they are most needed (Schupp, 2019).…”
Section: Marketplaces As Be Interventionsmentioning
confidence: 99%
“…Data from the ACS 2013-2017 five-year estimates at the census-tract level were used to approximate the boundaries of a neighborhood for the analysis. While there are many different conceptualizations in the literature as to how to measure a neighborhood, using census tracts as a proxy of a neighborhood has been shown to be an effective way to do this (Apparicio et al, 2007;Coulton et al, 2013;Hillier et al, 2011;Schupp, 2017). Two variables were created from the ACS.…”
Section: Applied Research Materialsmentioning
confidence: 99%
“…Farmers markets have been suggested as a promising method of direct marketing to contribute to increasing food access (Gillespie et al, 2008). This promise is based upon farmers markets' documented ability to provide diversified and healthy foods options and the low start-up and operational costs needed for market sessions, compared to brick-and-mortar alternatives (Govindasamy et al, 1998;Leiper & Clarke-Sather, 2017;Schupp, 2017).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…1 ). Although the USDA list is composed of self-reported markets and lacks systematic vetting to ensure accuracy (Schupp 2017 ), we assume that the inaccuracies are consistent across the US and from year to year, and so the USDA numbers adequately portray the patterns of expansion and stagnation, though not the precise number of US farmer markets in any given year.…”
Section: Introductionmentioning
confidence: 99%